Oral Administration of Human T-Cell Leukemia Virus Type 1 Induces Immune Unresponsiveness with Persistent Infection in Adult Rats - Kato, Hirotomo (American Society for Microbiology, 1998)
The major route of human T-cell leukemia virus type 1 (HTLV-1) infection is mother-to-child transmission caused by breast-feeding. We investigated the host immune responses to orally established persistent HTLV-1 infection in adult rats. HTLV-1-producing MT-2 cells were inoculated into immunocompetent adult rats either orally, intravenously, or intraperitoneally. HTLV-1 proviruses were detected in the peripheral blood and several organs for at least 12 weeks. Transmission of HTLV-1 to these animals was confirmed by analysis of HTLV-1 flanking regions. Despite persistent HTLV-1 presence, none of the orally inoculated rats produced detectable levels of anti-HTLV-1 antibodies, whereas all intravenously or intraperitoneally inoculated rats showed significant anti-HTLV-1 antibody responses. T-cell proliferative responses against HTLV-1 were also absent in orally inoculated rats. Our findings suggest that gastrointestinal exposure of adult rats to HTLV-1-infected cells induces persistent HTLV-1 infection in the absence of both humoral and cellular immune responses against HTLV-1. This immune unresponsiveness at primary infection may subsequently affect the host defense ability against HTLV-1.